The Federal Constitutional Court Rules for a Bright Future of Constitutional Pluralism. (March 2020) - Avbelj, Matej
Abstract: The ruling of the German Federal Constitutional Court in the Right to be forgotten II case is an example of constitutional pluralism in action. It demonstrates how a pluralist-minded court can elevate itself from and above the constitutional confines of its own legal order. By integrating the material standards of another legal order in its own review of constitutionality a national constitutional court contributes directly to the strengthening of the fundamental rights of individuals against the national authorities within the overall system of European legal order.